2011
DOI: 10.1007/s11739-011-0517-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of Th17 lymphocytes in the autoimmune and chronic inflammatory diseases

Abstract: The emerging role of interleukin-17 as a hallmark proinflammatory cytokine of the adaptive immune system produced by a new T helper cell subset termed "Th17" has received considerable attention. In this review we will focus on recent information regarding IL-17 and its relevance in autoimmune and chronic inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
82
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(87 citation statements)
references
References 51 publications
1
82
0
4
Order By: Relevance
“…Do niedawna sądzono, że limfocyty Th1 odgrywają główną rolę w patogenezie łuszczycy. Obecnie uważa się, że duże znaczenie ma także oś Th17/IL-23 [19,27]. Interleukina 23 jest wytwarzana przez komórki dendrytyczne i inne komórki prezentujące antygen.…”
Section: Rola Czynników Genetycznych I Epigenetycznychunclassified
See 3 more Smart Citations
“…Do niedawna sądzono, że limfocyty Th1 odgrywają główną rolę w patogenezie łuszczycy. Obecnie uważa się, że duże znaczenie ma także oś Th17/IL-23 [19,27]. Interleukina 23 jest wytwarzana przez komórki dendrytyczne i inne komórki prezentujące antygen.…”
Section: Rola Czynników Genetycznych I Epigenetycznychunclassified
“…Interleukina 23 w obecności transformującego czynnika wzrostu (ang. transforming growth factor -TGF-β), IL-1b, IL-6 oraz autokrynnej IL-21 uczestniczy w różnicowaniu i dojrzewaniu limfocytów Th17, podczas gdy TGF-β hamuje produkcję IL-22 [18,27]. Komórki Th17 wpływają na produkcję chemokin, peptydów przeciwbakteryjnych i innych cytokin prozapalnych oraz pojawienie się neutrofilów, ułatwiając szybki rozwój reakcji zapalnej w miejscu wniknięcia drobnoustrojów [22].…”
Section: Rola Czynników Genetycznych I Epigenetycznychunclassified
See 2 more Smart Citations
“…[4][5][6] Moreover, Ciprandi et al 5 revealed that serum IL-17 levels are also closely related to the clinical severity of AR. These results have indicated that Th17 may be involved in the immune response to casual allergens and could result in significant promotion of the severity of inflammatory disease.…”
mentioning
confidence: 99%